Production, Characterization, and Sensory Profiling of Novel Pepper Distilled Spirit - Yap Chin Ann; Foo See Wei; Gilbert Yeo; Teow Wei Ping; Lawrence Tuah (International Journal of Food Science)
This study described the production method of novel whiskey using black pepper berries as raw material including the determination of chemical composition and sensory profile of this distillate. The production process consisted of production of fermentation medium via hydrothermal treatment, followed by fermentation and distillation. The incorporation of hydrothermal extraction process makes this whiskey production process differ from the existing commercial spirit production protocol. Chemical composition analysis showed that there were 12 main volatile compounds that contribute to the aroma profile of this pepper whiskey which consisted of 1 aldehyde group, 3 ester groups, 2 phenolic compounds, and 6 alcohol groups. All of these compounds are presented at different concentrations that are able to give pleasant and signature aroma to this spirit. A 10-member descriptive analysis panel conducted showed that 7 descriptors can be used to define the organoleptic quality of this whiskey, namely, clarity and brilliance (visual), fruity and flora (aroma), spiciness and sweetness (taste), and fruity mouthfeels. In conclusion, pepper berries can be used as raw material for pepper whiskey production and having organoleptic quality acceptable for human consumption.